The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4304/jltr.5.2.348-359
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Attitudes towards Being Supervised in an EFL Context

Abstract: This study was an attempt to explore Iranian EFL teachers' attitude towards supervision and its influence on their classroom decision making. The study also examined the relationship between teachers' teaching experience and their attitude towards classroom supervision. 74 male and female English teachers holding BA, MA, or PhD degrees participated in this survey. Classroom observation and a teachers' questionnaire were used for the purpose of the study. The findings reveal that among the less experienced teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…In a recent inquiry, Lasagabaster and Sierra (2011) documented that the majority of Spanish EFL teachers held positive attitudes towards classroom observation as the advantages of observation prevail over the disadvantages in their minds although anxiety-provoking nature of observation and time constraints led to limited willingness to take part in possible observation activities. More recently, Rahmany, Hasani, and Parhoodeh (2014) found that less experienced teachers with less than five years of teaching experience were more influenced by the supervision process in terms of making decisions in the classroom whereas teachers with six to ten years of teaching experience looked like to be the most worrywarts.…”
Section: Background To the Studymentioning
confidence: 99%
“…In a recent inquiry, Lasagabaster and Sierra (2011) documented that the majority of Spanish EFL teachers held positive attitudes towards classroom observation as the advantages of observation prevail over the disadvantages in their minds although anxiety-provoking nature of observation and time constraints led to limited willingness to take part in possible observation activities. More recently, Rahmany, Hasani, and Parhoodeh (2014) found that less experienced teachers with less than five years of teaching experience were more influenced by the supervision process in terms of making decisions in the classroom whereas teachers with six to ten years of teaching experience looked like to be the most worrywarts.…”
Section: Background To the Studymentioning
confidence: 99%
“…That is, more experienced teachers are more likely to be reflective and think about their performance, participate further in the decision-making process, and are generally more successful in teaching (Richards & Farrell, 2005). According to the findings offered by Rahmany, Hasani, & Parhoodeh (2014), the classroom observation along with the supervision of the teacher's performance plays an important role in the decision-making process of inexperienced teachers; since this group of teachers has a positive attitude towards the role of the supervisor. Moreover, the results of the current study are in line with the findings of Garrett & Steinberg (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given this awareness, teachers improve certain skills and methods, promote their teaching performance, and gain more useful working experiences. According to Rahmany et al (2014), classroom observation and collecting information based on pre-determined assessment criteria given positive feedback to teachers, which leads to the improvement of the teachers' professional performance and the students' learning as a result. In a similar vein, Williams (1989) also discussed that if the main objective of observation is the improvement of the teaching performance and not making a judgment about their teaching method, it provides great opportunities for the teachers, which ultimately results in an increase in their awareness and ability to evaluate their own teaching method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Kilminster et al (as cited in Muttar & Mohamed, 2013) supervision is the "provision of guidance and feedback on matters of personal, professional and educational development in the context of trainee's experience taking place" (p. 2). Rahmany, Hasani, & Parhoodeh (2014) consider it as a tool commonly used in education to support understanding and development. In their point of view, it includes "monitoring and analyzing classroom teaching practice and gathering appropriate data according to standards set by the administrator with the aim of providing meaningful feedback and direction to teachers to improve teaching and accordingly learning process" (p. 349).…”
Section: Instructional Supervisionmentioning
confidence: 99%